Analisis Work Life Balance Karyawan di Wirman Sambal - Kasmawati Kasmawati; Yobert Kornelius; Harnida Wahyuni adda; Suryadi Samudra (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2024)
This research focuses on analyzing the work-life balance of employees at Usaha Wirman Sambal. In the context of the success of an organization, human resources play a crucial role. This business prioritizes the quality of chili sauce, requires employees with superior qualifications and optimal performance. Work-life balance is in the spotlight when facing complex work demands. This research is important because it impacts employee well-being, productivity and organizational competitiveness. Work-life balance is not just time allocation, but includes aspects of physical, mental health and the quality of social relationships. Increasing employee well-being contributes positively to productivity and performance. In the research "Analysis of Work-Life Balance of Employees at Wirman Sambal," the question explains how employees at Wirman Sambal maintain a balance between their work and personal lives. As well as what main challenges are faced by employees at Wirman Sambal in achieving Work-Life Balance. The research method uses qualitative methods with data collection techniques through interviews and observations. The results of interviews and observations revealed diverse approaches to achieving work-life balance, including schedule planning, implementing time limits, and open communication. Key challenges involve changing schedules, increased workloads, limited time flexibility, and the impact of technology. Understanding these factors provides insight into formulating policies and practices that support work-life balance. A well-managed work-life balance at Wirman Sambal has a positive impact on employee welfare and productivity, creates a positive work culture, and improves the overall quality of life. This research contributes to the understanding of work-life balance in the context of the culinary industry and offers constructive recommendations for improving policies and practices in these work environments.